2022
DOI: 10.1007/s40121-022-00591-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Emerging Multidrug-Resistant Pseudomonas aeruginosa

Abstract: Multidrug-resistant (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa isolates are frequent causes of serious nosocomial infections that may compromise the selection of antimicrobial therapy. The goal of this review is to summarize recent epidemiologic, microbiologic, and clinical data pertinent to the therapeutic management of patients with infections caused by MDR/XDR-P. aeruginosa. Historically, conventional antipseudomonal b-lactam antibiotics have been used for the empiric treatment of MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 121 publications
(135 reference statements)
1
80
0
2
Order By: Relevance
“…Regarding the last section of our work, the clinical-epidemiological threat posed by increasing rates of antibiotic resistance in P. aeruginosa and other species has been partially alleviated by the introduction of novel β-lactam–β-lactamase inhibitor combinations such as TOL-TAZ, CAZ-AVI, imipenem-relebactam, and others still in clinical development (e.g., meropenem-vaborbactam, meropenem-nacubactam, cefepime-taniborbactam, and cefepime-zidebactam [ 54 , 55 ]). Although these therapies displayed encouraging levels of effectiveness from the first moment, P. aeruginosa has repeatedly shown the capacity to develop resistance to CAZ-AVI and TOL-TAZ through different mechanisms, posing a real danger to the long-term efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the last section of our work, the clinical-epidemiological threat posed by increasing rates of antibiotic resistance in P. aeruginosa and other species has been partially alleviated by the introduction of novel β-lactam–β-lactamase inhibitor combinations such as TOL-TAZ, CAZ-AVI, imipenem-relebactam, and others still in clinical development (e.g., meropenem-vaborbactam, meropenem-nacubactam, cefepime-taniborbactam, and cefepime-zidebactam [ 54 , 55 ]). Although these therapies displayed encouraging levels of effectiveness from the first moment, P. aeruginosa has repeatedly shown the capacity to develop resistance to CAZ-AVI and TOL-TAZ through different mechanisms, posing a real danger to the long-term efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular studies have revealed that increased efflux pumps are a popular and criticizing resistance mechanism in microbial biofilms [ 102 ]. This mechanism has been extensively studied in a commonly found biofilm-producing P. aeruginosa pathogen [ 103 ]. The PA1874-1877 (cluster of genes) involved in developing resistance in biofilms was discovered by Zhang and Mah.…”
Section: Resistance Mechanism In Biofilmsmentioning
confidence: 99%
“…Carbapenem was once considered the most effective antibiotic for multidrug-resistant bacterial infections, but increasing resistance rates indicate that carbapenem-resistant organisms (CRO) have emerged as a frequent and challenging problem around the world [ 1 , 2 ]. CRO comprise lethal pathogens such as carbapenem-resistant Klebsiella pneumoniae (CRKP), Acinetobacter baumannii (CRAB) and Pseudomonas aeruginosa , resulting in increasing morbidity given the lack of safe and effective antibiotics [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%